Pengaruh Brand Image, Kualitas Produk Dan Harga Terhadap Keputusan Pembelian (Studi Kasus Pada Konsumen Tas Eiger Mahasiswa Penghuni Kost Di Kelurahan Dinoyo) - Ali Muhammad Farid; M Hufron; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTBased on research carried out with the aim of analyzing the influence of brand image, product quality and price on purchasing decisions on consumer eiger bags for boarding students in dinoyo village, amounting to 374 people. The sampling technique used is proportional stratified random sampling in which the technique is to select samples based on class. The analytical method used in this study is multiple linear regression analysis with hypothesis testing using the t test and f test. These results indicate that brand image, product quality and price influence purchasing decisions. brand image has a partial effect on purchasing decisions, product quality has a partial effect on purchasing decisions, and Price has a partial effect on purchasing decisions. Keywords: Brand Image, Product Quality, Price, Purchase Decision